Preconceptional and Periconceptional Folic Acid Supplementation in the Visegrad Group Countries for the Prevention of Neural Tube Defects - Rísová, Vanda; Saade, Rami; Jakuš, Vladimír; Gajdošová, Lívia; Varga, Ivan; Záhumenský, Jozef (Nutrients, 2024)
Neural tube defects (NTDs) are malformations of the central nervous system that represent the second most common cause of congenital morbidity and mortality, following cardiovascular abnormalities. Maternal nutrition, particularly folic acid, a B vitamin, is crucial in the etiology of NTDs. FA plays a key role in DNA methylation, synthesis, and repair, acting as a cofactor in one-carbon transfer reactions essential for neural tube development. Randomized trials have shown that FA supplementation during preconceptional and periconceptional periods reduces the incidence of NTDs by nearly 80%. Consequently, it is recommended that all women of reproductive age take 400 µg of FA daily. Many countries have introduced FA fortification of staple foods to prevent NTDs, addressing the high rate of unplanned pregnancies. These policies have increased FA intake and decreased NTD incidence. Although the precise mechanisms by which FA protects against NTDs remain unclear, compelling evidence supports its efficacy in preventing most NTDs, leading to national recommendations for FA supplementation in women. This review focuses on preconceptional and periconceptional FA supplementation in the female population of the Visegrad Group countries (Slovakia, Czech Republic, Poland, and Hungary). Our findings emphasize the need for a comprehensive approach to NTDs, including FA supplementation programs, tailored counseling, and effective national-level policies.
Keywords: defekty neurální trubice; Preconception Care; kyselina listová; Pregnancy; Humans; supplementation; prevention; Neural Tube Defects; Female; Folic Acid; Polsko; folic acid; fyziologie výživy v mateřství; lidé; Poland; recommendations; Maternal Nutritional Physiological Phenomena; ženské pohlaví; péče před početím; těhotenství; Czech Republic; potravní doplňky; Dietary Supplements; Česká republika; polymorphisms; fortification; neural tube defects